Who has the greatest influence on adolescent gaming disorder: parents, teachers, or peers? An interpersonal relationships network model of gaming disorder - Tan, Xinjie; Liu, Chunlin; Yang, WanJun; Hui, Xiao; Zhang, Ling; Chen, Shuanghong; He, Ying (Frontiers in Psychiatry, 2024)
Introduction: Gaming disorder (GD) in adolescents is associated with impaired interpersonal relationships, including those with parents, teachers and peers. However, the interpersonal relationships most strongly associated with GD-related maladaptive behaviors are not well established. This study aimed to investigate the associations between these three types of relationships and the manifestation of GD in adolescents.Methods: In this cross-sectional study, 1920 Chinese adolescents participated in a survey that assessed interpersonal relationships (parent-child, teacher-student, and peer relationships) and demographic variables (e.g., gender, grade, duration of gaming), and 1414 participants were ultimately included. A network analysis approach was utilized to evaluate the key network metrics of edge weight and node centrality.Results: The findings revealed that peer fear and inferiority (r = 0.12) and teacher-student conflict were most strongly correlated with GD, followed by parent-child conflict (r = 0.09). Peer fear and inferiority exhibited the highest strength centrality (0.84), followed by teacher-student conflict (0.83) and parent-child conflict (0.35). Moreover, the duration of gaming was significantly and positively correlated with GD (r = 0.19).Conclusions: The present study underscores the significant role of conflict and rejection within interpersonal relationships, particularly among peers, in the manifestation of GD-related behaviors in Chinese adolescents.